Study of the patterns of media frames used in the production of Arabic spring breaks in Al Arabiya channel - عبد الرحمن ايمان (ALBAHITH ALALAMI, 2014)
production of the spot in the news channels - a study of patterns of spot media used in the production of spring breaks Arab Al-Arabiya The spacers news in Arabic, one of the messages that seek channel output are fit and policy on the one hand and meet the needs of viewers for information intensive and image influential to find out the latest developments on the Arab arena, especially the Syrian revolution on the other and thus The viewer for the type of coverage the stomach through a newsletter about the event on the one hand to keep following up on her and eager to watch the other hand And sought search through the random sample Almenttma to analyze spacers news over the three years of the Revolution, totaling sixty watershed chronicles analysis of the categories of how it was said and what was said to know the most important spammers media used by the channel in the production of separators news has been found through research that Arabic was used as part of the conflict Capers kinds of spammers media in the production of breaks which is in line with the quality of the event under study as Asnkhaddmt Arabic more means protruding stir in television , a picture with a number of types of Qtadtha the most commonly used music to fill them from a significant effect on the viewer in the consolidation of the event in his mind and stir sympathy Arab and tried through its production of breaks the news to the personalization of the event, whether what is happening to lay down dependency on a limited number of persons or parties, or by selecting the places of conflict in certain areas and neglecting other areas